Visualization Strategy: An Effective Strategy to Teach Reading to Middle School Students - Adenan Damiri; Tommy Hastomo; Yeti Aprita Sari (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2022)
This research was conducted to know the influence of the Visualization Strategy on students' reading comprehension of recount text. This study aimed to identify and describe the impact of the Visualization Strategy on students' reading comprehension. The researchers utilized a quasi-experimental method in this study. There were 283 students in nine classes. Cluster Random Sampling Technique was used to collect the sample. The sample consisted of two classes, with the following details: the first class was an experimental class of 31 students, while the second class was a control class of 31 students. The primary technique of this research was a reading test in multiple choices, which consisted of 40 items with four options. In analyzing the data, the researchers used the t-test formula. The findings show that the Visualization Strategy impacted students' reading comprehension at SMP Negeri 32 Bandar Lampung in 2021/2022. It can be seen from the result that the mean score of post-test in the experimental class (84.42) is higher than the mean score of post-test in the control class (72.54). Therefore, using a visualization strategy as a learning model is more effective than a conventional strategy. On the other hand, the pre-test score in the experimental class is 67.42 before utilizing the visualization approach, and the mean score for the post-test in the experimental class is 84.42. It indicates Visualization Strategy had a beneficial impact on reading comprehension, so the students can improve their reading skills using this learning strategy Keywords: Visualization Strategy, Reading Comprehension, Experimental Research